2021
DOI: 10.1101/2021.05.19.21257439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid And high throughput RT-qPCR assay for identification and differentiation between SARS-CoV-2 variants B.1.1.7 and B.1.351

Abstract: Emerging SARS-CoV-2 (SC-2) variants with increased infectivity and vaccine resistance are of major concern. Rapid identification of such variants is important for the public health activities and provide valuable data for epidemiological and policy decision making. We developed a multiplex quantitative RT-qPCR (qPCR) assay that can specifically identify and differentiate between the emerging B.1.1.7 and B.1.351 SC-2 variants. In a single assay, we combined four reactions: one that detects SC-2 RNA independentl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…RNA from PCR-positive specimens are screened for specific spike gene mutations by PCR using the Seegene Novaplex SARS-CoV-2 variants I assay that detects RdRp (positive control) and the following changes in the spike protein: N501Y and HV 69/70 deletion indicative of Alpha, and E484K and N501Y indicative of Beta (Seegene Inc., Seocho-gu, Seoul, 06646, South Korea). The central laboratory recently developed a unique assay that specifically detects variant Beta [24] . WGS is then conducted at MoH qualified laboratories that participate in the national sequencing consortium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA from PCR-positive specimens are screened for specific spike gene mutations by PCR using the Seegene Novaplex SARS-CoV-2 variants I assay that detects RdRp (positive control) and the following changes in the spike protein: N501Y and HV 69/70 deletion indicative of Alpha, and E484K and N501Y indicative of Beta (Seegene Inc., Seocho-gu, Seoul, 06646, South Korea). The central laboratory recently developed a unique assay that specifically detects variant Beta [24] . WGS is then conducted at MoH qualified laboratories that participate in the national sequencing consortium.…”
Section: Methodsmentioning
confidence: 99%
“…By Jun 27, 2021, Beta was reported in 97 countries [22] with local transmission reported in Canada, Germany, the United Kingdom, and the United States [23] . Beta was first reported in Israel on Dec 29, 2020 [24] . An Israeli study reported that a higher proportion of vaccine breakthrough cases were Beta compared to other strains [25] .…”
Section: Introductionmentioning
confidence: 99%